2019
DOI: 10.1186/s12885-019-5546-z
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy and patient participation in multidisciplinary tumor conferences in breast cancer care: a multilevel modeling approach

Abstract: Background Decisions made in multidisciplinary tumor conferences (MTC) that consider patient preferences result in better patient outcomes. Furthermore, it has been shown that in some breast cancer centers in Germany, patients participate in MTCs and that participation is associated with sociodemographic and breast cancer center-related factors. Health literacy (HL) has been shown to be predictive for individual health behavior and is an important prerequisite for patient participation in healthca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 46 publications
1
33
1
1
Order By: Relevance
“…According to the accreditation criteria of the Medical Council Westphalia‐Lippe, Germany, patients should be allowed to participate in an MTC during the discussion of their own case if they desire. However, only about 5%‐7% of breast cancer patients in Germany actually make use of this offer 25,29,34 . At the moment, little is known about patient participation in MTCs and its effect on patients' needs and emotions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the accreditation criteria of the Medical Council Westphalia‐Lippe, Germany, patients should be allowed to participate in an MTC during the discussion of their own case if they desire. However, only about 5%‐7% of breast cancer patients in Germany actually make use of this offer 25,29,34 . At the moment, little is known about patient participation in MTCs and its effect on patients' needs and emotions.…”
Section: Introductionmentioning
confidence: 99%
“…However, only about 5%-7% of breast cancer patients in Germany actually make use of this offer. 25,29,34 At the moment, little is known about patient participation in MTCs and its effect on patients' needs and emotions. Own prior research focused on the patient perspective concerning patient participation in an MTC and provided first indications of a mixed picture of positive and negative cognitive and emotional experiences of breast cancer patients.…”
mentioning
confidence: 99%
“…Furthermore, our results expand the findings from previous international research concerning the reasons for differences in MTCpp between cancer centers. Previous German studies have shown significant differences in the frequency of MTCpp between breast cancer centers 31,33 but could not explain them. We were able to explain potential reasons for these differences by studying the providers' experienced external factors, attitudes and goals concerning the feasibility of MTCpp.…”
Section: Differences In Mtc Patient Participation Between Organizationsmentioning
confidence: 71%
“…Previous studies have shown that in Germany, participation is a rare but constant reality in healthcare, with 5–7% of breast cancer patients participating in MTCs, regardless of the certification program. 31–33 The results of these studies also suggest that MTCpp varies by patient characteristics and between the breast cancer centers themselves. 31 , 33 So far, no explanations for the variation between organizations as well as the feasibility of MTCpp from the providers’ perspective exist.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation